60.7k views
5 votes
What is
(3xy-1) (4xy+2)

User Eric MC
by
5.3k points

2 Answers

2 votes

12x^2y^2+2xy-2 with problems like these use the app “Photomath” it will help you a lot.

User Nadun
by
5.5k points
2 votes

Hello!

The answer is:


(3xy-1)(4xy+2)=12(xy)^(2)+2xy-2

or


(3xy-1)(4xy+2)=12x^(2)y^(2)+2xy-2

Why?

To solve the problem and identify the resultant expression, we need to apply the distributive property, and the, add or subtract like terms.

Describing the distributive property:


(a+b)(c+d)=a*c+a*d+b*c+b*d

Remember, like terms are the terms that share the same variable and same exponent, for example:


a^(2) +3a^(2)+a^(3)=4a^(2)+a^(3)

We were able to add only the terms that have the same exponent (2).

We are given the expression:


(3xy-1)(4xy+2)

Now, solving we have:


(3xy-1)(4xy+2)=(3xy*4xy)+(3xy*2)-(1*4xy)-2\\\\(3xy*4xy)+(3xy*2)-(1*4xy)-2=12(xy)^(2)+6xy-4xy-2\\\\12(xy)^(2)+6xy-4xy-2=12(xy)^(2)+2xy-2

Hence, we have that:


(3xy-1)(4xy+2)=12(xy)^(2)+2xy-2

or


(3xy-1)(4xy+2)=12x^(2)y^(2)+2xy-2

Have a nice day!

User Jpsimons
by
5.1k points